Design of a lift reduction device for passenger car - Gobinath, Raman (2010)
The performance and handling of automobile are significantly affected by its aerodynamic properties. One of the main causes of aerodynamic is about lifting force. This will influence all the aspect of the vehicles such as overall performance, fuel consumption, safety and stability. The addition of rear spoiler to an aerodynamically optimized car body, leads to decrease lift coefficients. In an aerodynamic field, the main important thing to get the stability and performance is to design a vehicle with low CL. The reduction of lift and flow separation is the key results that will be a point of discussion. Rear spoiler will reduce the flow separation at the trunk that causing the turbulent airflow. The wake region also will be reduced and this will make the lift force that produce at the rear trunk will reduce. The task was done by doing a Computational Fluid Dynamic (CFD) analysis for expected vehicle speed of 110 km/h. A lift force and drag force was obtained based on inputs from CFD analysis. This force was used to calculate the lift and drag coefficient of the model as a whole. The approach needed to justify the amount of lift that can be reduced by addition of a rear spoiler as compared to the model without the rear spoiler. This project is to get an overall comparison of the pressure distribution before and after the rear spoiler is added. Five different type of rear spoiler designed to study its effect on passenger car. The lift coefficient of the vehicle was minimized up to 0.0405 (case 4) by adding rear spoiler from 0.2036 without spoiler (case 1). This is due to the design type of spoiler in case 4 which cause greater pressure coefficient on upper wing of rear spoiler.